Sustainable synthesis of bakuchiol-mediated gold nanoparticles for drug delivery against bacterial strains and tumor microenvironments, and its in silico target proteins identification - Mishra, Pooja; Faruqui, Tabrez; Khanam, Sheeba; Khubaib, Mohd; Ahmad, Irfan; Saeed, Mohd; Khan, Salman (Frontiers in Molecular Biosciences, 2024)
Introduction The sustained synthesis of gold nanoparticles (GNPs) has gained significant attention in biomedical applications. In this study, we explored the antibacterial and anticancer potential of bakuchiol-mediated gold nanoparticles (Bak-GNPs). Bakuchiol, a natural compound found in Psoralea corylifolia seeds, serves as both a reducing and stabilizing agent for green synthesis of GNPs. Our objectives include network analysis, molecular docking, synthesis of GNPs, characterization, and antipathogenic and anticancer efficacy of Bak-GNPs against lung and liver cancers. Methods Protein-protein interaction networks were analyzed to identify effective protein targets for bakuchiol in lung and liver cancers. A molecular docking study was performed to validate the efficacy of the target protein against lung and liver cancer. Furthermore, Bak-GNPs were synthesized using bakuchiol and characterized by various techniques such as UV-visible spectroscopy, dynamic light scattering (DLS), zeta potential transmission electron microscopy (TEM), and Fourier-transform infrared (FTIR) spectroscopy, and their potential against pathogens and lung and liver cancers. Results GNAI3 emerged as the most promising target, with a binding energy of −7.5 kcal/mol compared to PTGER3’s −6.9 kcal/mol, different characterization techniques revealed the successful synthesis of Bak-GNPs. Bak-GNPs exhibited potent antibacterial activity against both Gram-positive and Gram-negative bacteria, as confirmed by minimum inhibitory concentration (MIC) values. Bak-GNPs demonstrated significant anticancer effects on A549 (lung cancer) and HepG2 (liver cancer) cells, with IC50 values of 11.19 μg/mL and 6.6 μg/mL, respectively. Induction of apoptosis and inhibition of cell proliferation were observed in both the cell lines. The increased production of reactive oxygen species (ROS) contributes to its anticancer effects. Discussion This study highlights promising biomedical applications of bakuchiol-mediated GNPs. This green synthesis approach using bakuchiol provides a sustainable method for producing nanoparticles with enhanced biological activities. Further exploration of the pharmacological properties and mechanisms of Bak-GNPs is required to optimize their therapeutic efficacy for clinical use.